2018
DOI: 10.1007/s00401-018-1920-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in Alzheimer’s disease and common neuropathologies of aging

Abstract: Alzheimer’s dementia is significantly more common in women than in men. However, few pathological studies have addressed sex difference in Alzheimer’s disease (AD) and other brain pathologies. We leveraged post mortem data from 1453 persons who participated in one of two longitudinal community-based studies of older adults, the Religious Orders Study and the Rush Memory and Aging Project. Postmortem examination identified AD pathologies, neocortical Lewy bodies, DNA-binding protein 43 (TDP-43), hippocampal scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
193
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 220 publications
(213 citation statements)
references
References 66 publications
(132 reference statements)
15
193
4
1
Order By: Relevance
“…Sex differences in amyloid deposition have been inconsistent in the literature. Here, we found that females had slightly greater amyloid ( p = 0.045) in comparison to males, which is consistent with the borderline findings in a large postmortem study . Our group and others have shown that amyloid burden at baseline was associated with greater rate of cognitive decline and increased risk of dementia …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sex differences in amyloid deposition have been inconsistent in the literature. Here, we found that females had slightly greater amyloid ( p = 0.045) in comparison to males, which is consistent with the borderline findings in a large postmortem study . Our group and others have shown that amyloid burden at baseline was associated with greater rate of cognitive decline and increased risk of dementia …”
Section: Discussionsupporting
confidence: 91%
“…Here, we found that females had slightly greater amyloid (p = 0.045) in comparison to males, which is consistent with the borderline findings in a large postmortem study. 43 Our group and others have shown that amyloid burden at baseline was associated with greater rate of cognitive decline and increased risk of dementia. 2,3,[44][45][46][47] The growth curve modeling approach allowed us to observe 2 phenomena with respect to the amyloid pathway and cognitive decline.…”
Section: Amyloidosis and Cognitive Declinementioning
confidence: 87%
“…Sex difference is becoming focused in AD research field. 25,26 A new cohort with increased samples will help us to understand the effects of sex on outcomes. We could not measure blood glucose levels during the course of our study until 18 months of age, because any stressful or invasive procedure might have impacts on lifespan of our mice.…”
Section: App Nl-f/wt Knock-in; Ob/ob Mice Despite the Minimal And Comentioning
confidence: 99%
“… Abstract Sex differences in the manifestations of Alzheimer’s disease (AD) are under intense investigations 1,2 . Despite the emerging importance of polygenic predictions for AD 38 , the sex-dependent polygenic effects have not been demonstrated.…”
mentioning
confidence: 99%
“…Evidence on sex-dependent clinicopathological progressions of Alzheimer’s disease (AD) is just beginning to emerge 2 . Compared to men, women show later manifestation of verbal memory deficits 10 , faster decline after disease onset 11 , and some differences in neuropathological characteristics, such as tau tangle density 1,12 . Results from studies on incidence rate and prevalence are less consistent 13,14 , yet women are often reported to have increased incidence of AD in older ages 15 and higher prevalence 16 .…”
mentioning
confidence: 99%